Development of a Textbook on the History of Economic Thought with a Combination of Barcode Video in the Application of Differentiated Learning - Andriansyah, Eka Hendi; Prakoso, Albrian Fiky; RoziqiFath, Zain Fuadi Muhammad; Ginanjar, Ardhita Eko; Srisuk, Prattana (IKIP Widya Darma Surabaya, 2024)
Objectives: This research is to facilitate the diversity of student conditions in learning and can even be used simply for students with special needs at a low level such as deaf students and other limitations that can still be facilitated with a combination of audio visual media. Method: The type of research method used in this study is a research and development design . Reaserch and development is a research method used to produce a certain product and test the effectiveness of the product. The development model used in this study is a development research model by proposing a series of stages that must be taken in this approach, including research and information collecting, planning, developing preliminary form of product, preliminary field testing, main product revision, main field testing, operational product revision, operational field testing, final product revision, and dissemination and implementation. Results: Based on the results of validation that have been carried out by experts in media, language, and materials, as well as in limited trials, this book is considered very good and worthy of application in learning. The integration of technology in this textbook reflects significant developments in the development of interactive and digital educational resources. Novelty: A combination of video barcodes in diverse learning contexts This innovative approach combines digital technology with traditional teaching materials, so students can choose the most effective way of learning according to their learning style. Either visually, auditory, or kinesthetic. Thus, the ADDIE model is used to develop textbooks in getting positive assessments from each expert and limited trials. This shows that the approach is not only innovative, but also effective and suitable for application in the field of education.